2017
DOI: 10.1016/j.rvsc.2017.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Experimental co-infection of infectious bronchitis and low pathogenic avian influenza H9N2 viruses in commercial broiler chickens

Abstract: In this study, commercial broilers were experimentally infected with single (classical IBV, variant IBV or AIV-H9N2) or mixed AIV-H9N2 with classical, variant or vaccine strains of IBV. Birds were monitored for clinical and pathological outcomes and virus shedding for 10days post infection (DPI). Clinical signs were limited to the respiratory tract in all challenged groups and varied from mild to moderate mouth breathing to severe respiratory signs with snorting sound and extended head. Mortalities were only r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 26 publications
8
45
1
Order By: Relevance
“…Previous studies have indicated the synergistic mechanism between IBV and AIV-H9N2, possibly by trypsin-like proteases encoded by coronaviruses that enhance the AIV-H9N2 hemagglutinin cleavage (Haghighat-Jahromi et al, 2008;Hassan et al, 2017), which increases replication and pathogenicity of AIV-H9N2. In this study, we did not find any synergistic effects on pathogenicity when different types of IBV co-infected SPF chickens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated the synergistic mechanism between IBV and AIV-H9N2, possibly by trypsin-like proteases encoded by coronaviruses that enhance the AIV-H9N2 hemagglutinin cleavage (Haghighat-Jahromi et al, 2008;Hassan et al, 2017), which increases replication and pathogenicity of AIV-H9N2. In this study, we did not find any synergistic effects on pathogenicity when different types of IBV co-infected SPF chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from epidemiological studies has revealed that co-infection with IBV and other respiratory pathogens, such as avian influenza virus (AIV) H9 subtype, is widespread in poultry in Jordan and Egypt (Roussan et al, 2008;Hassan et al, 2017). It is also reported that coinfection with different IBV serotypes is occasionally observed in the same chicken flock (Dolz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, co-infections of LPAIV H9N2 with other respiratory pathogens, particularly with IBV, Mycoplasma gallisepticum, Staphylococcus aureus, Avibacterium paragallinarum, Escherichia coli, Ornithobacterium rhinotracheale and/ or immunosuppressive agents can exacerbate LPAIV H9N2 infections and result in severe clinical disease with different rates of mortality (Nili & Asasi, 2002;Kishida et al, 2004;Perk et al, 2006). Previous studies have demonstrated longer H9N2 virus shedding, more severe clinical signs and higher mortality rates caused by a co-infection with LPAIV H9N2 and IBV, either as a vaccine or as a wild-type virus (Seifi et al, 2012;Hassan et al, 2017;Ismail et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Such cell receptor also serves as a receptor protein determinant for primary attachment of group 3 corona viruses [7], allowing fusion events and entry of both viruses. Huang et al have described as it is unknown whether co-infections with AIV and IBV exacerbate clinical signs of the disease in infected birds or produce viral interference, masking infections by either virus [8], even though it is reported that co-infection of IBV with AIV increased not only the severity of AIV-H9N2 clinical sings and gross lesions, but also the mortality rate with extended viral shedding period of AIV [9][10][11].…”
Section: Introductionmentioning
confidence: 99%